Optimization of Algorithms in Relation to iBeacon - Budina, Jan; Zmitko, Martin; Kříž, Pavel (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
The boom of portable electronics and high-speed wireless networks has brought changes throughout society, including development in positioning systems. Indoor localization is more and more important. With modern technology, we are able to track people in shopping complexes and offer them discounts for surrounding goods. The following text deals with the design and description of methods to determine user’s position based on fingerprint technology. The text focuses on the description of algorithms in relation to the iBeacon. Three main algorithms were described in the text. The following text describes the implementation of Knn algorithm. The main goal of this paper is to clearly describe the basic positioning algorithms for the readers, introduce implementation of the Knn algorithm and its usage in real environment.